Reengineering of Student-Teacher Coding Program for Philippine Grade Schools Curriculum: A Literature Review - Zamora, Princess Arleen; Bautista, Nora; Carpio, Joselito (JPAIR Multidisciplinary Research, 2024)
The main objective of this literature review is to delve into the situation of coding programs in schools in the Philippines, examining both the obstacles they encounter and potential areas for improvement. By analyzing a range of studies, scholarly articles, and relevant literature, this research aims to comprehend how coding programs impact students' acquisition of skills, logical reasoning abilities, creativity, and cognitive development. Moreover, it evaluates approaches and best practices for integrating coding courses into the curriculum while considering the advantages and challenges associated with their implementation. In addition, the study explored how students' academic performance and future job prospects are influenced by their coding skills and proposed strategies to enhance coding programs that promote the development of these abilities. The insights gathered from this analysis provide recommendations for research and valuable insights into designing coding curricula that cater specifically to elementary schools in the Philippines within the broader educational landscape.
Keywords: Coding Programs; Education; Skill Development; Logical Reasoning; Creativity; Cognitive Development; Curriculum Integration